Book Review: M. HEBBLEWHITE, The Emperor and the Army in the Later Roman Empire, AD 235-395, London- New York 2017 - STEWART, Michael Edward (Byzantina Symmeikta, 2018)
Review: M. HEBBLEWHITE, The Emperor and the Army in the Later Roman Empire, AD 235-395, London- New York 2017